A report on the White-winged Wood Duck in southern Sumatra - Holmes, D A (Wildfowl, 1977)
The habitat, nest sites and possible population of the White-winged Wood Duck Cairina scutulata in southern Sumatra are discussed. Surveys are required to discover more from the area.